Change in global freshwater storage - McCartney, Matthew P.; Rex, William; Yu, Winston; Uhlenbrook, Stefan; Gnechten, Rachel von (International Water Management Institute, 2022)
Freshwater in both natural and man-made stores is critical for socioeconomic development. Globally, cumulative reduction in terrestrial water storage from 1971 to 2020 is estimated to be of the order of 27,079 Bm3. Although insignificant in comparison to the total volume stored, the decrease in ‘operational’ water stored (i.e., the proportion of water storage that is sustainably utilizable by people) is estimated to be of the order of 3% to 5% since 1971. In many places, both natural and man-made water storage are declining simultaneously, exacerbating water stress. Conjunctive use of different water stores is a prerequisite for water security and it is vital that natural water stores are fully integrated, alongside man-made water infrastructure, in future water resources planning and management.